2006
DOI: 10.1159/000095704
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Effects of Unilateral Subthalamic Nucleus Deep Brain Stimulation in Advanced Parkinson’s Disease

Abstract: To investigate the bilateral effects of unilateral subthalamic nucleus deep brain stimulation (STN-DBS), we prospectively studied 9 consecutive advanced Parkinson’s disease (PD) patients (2 men and 7 women) who underwent unilateral STN-DBS. Patients were evaluated preoperatively and at 3 and 6 months postoperatively with and without dopaminergic medications (‘on’ and ‘off’ medication, respectively). Postoperatively, patients were assessed with and without stimulation. We found that, when compared with baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
57
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 27 publications
(18 reference statements)
18
57
3
1
Order By: Relevance
“…In addition, improvement of brainstem structures such as pedunculopontine nuclei plays an indispensable role in improvement of axial and gait disturbances [1,3,28]. Our data support further speculation that mutual connections at both sides of basal ganglia and thalamic nuclei might explain improvement of both sides in unilateral DBS.…”
Section: Contralateral Gpi Deactivationsupporting
confidence: 83%
See 3 more Smart Citations
“…In addition, improvement of brainstem structures such as pedunculopontine nuclei plays an indispensable role in improvement of axial and gait disturbances [1,3,28]. Our data support further speculation that mutual connections at both sides of basal ganglia and thalamic nuclei might explain improvement of both sides in unilateral DBS.…”
Section: Contralateral Gpi Deactivationsupporting
confidence: 83%
“…Therefore, our study was limited to patients with unilateral DTN-DBS. Previous reports have described that unilateral STN-DBS improved the UPDRS motor scale from 23 % to 43 % [3,6,12,16]. Our patients exhibited greater improvement (50 %) than those probably because our patients had marked asymmetric symptoms and rather milder impairments.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…However, unilateral STN DBS was found to yield similar effects to unilateral GPi DBS on tests of contralateral fine motor function. 63 Unilateral STN DBS improved 'off' motor UPDRS scores by 26%, 64 31%, 65 and 37%, 66 remarkably similar to the results with unilateral pallidotomy. Samii et al 67 found an improvement in 'off' motor UPDRS scores of 25% with unilateral STN DBS, increasing to 43% when the contralateral side was added, stressing that one of the advantages of DBS is that it can be performed bilaterally, but that the results are not simply twice as good as unilateral surgery because of axial as well as ipsilateral effects of unilateral STN DBS (as seen by others as well).…”
Section: Is Dbs a Safer And More Effective Therapy For Pd?supporting
confidence: 52%